Emergence of ozone recovery evidenced by reduction in the occurrence of Antarctic ozone loss saturation. Issue 1 (December 2018) - Kuttippurath, J.; Kumar, P.; Nair, P.; Pandey, P.
Abstract Industrial emissions of ozone depleting substances (ODSs) during the second half of the twentieth century have led to one of the most visible human impacts on the Earth: the Antarctic ozone hole. The ozone loss intensified in the 1980s and reached the level of saturation (i.e., complete loss of ozone) due to the high levels of ODSs in the atmosphere. Significant changes in the southern hemispheric climate have been observed in the past decades due to this unprecedented ozone loss. Although the most recent studies suggest healing in the Antarctic ozone hole, the status of ozone in the loss saturation layer ( 13–21 km) has not been discussed in detail. Here, a comprehensive analysis of vertical, spatial and temporal evolution of ozone loss saturation (ozone mixing ratio ≤ 0.1 ppmv) in the Antarctic vortex using high resolution measurements for the 1979–2017 period reveals that the loss saturation began in 1987 and continued to occur in all winters thereafter, except in the major warming winters of 1988 and 2002. However, our analysis shows a clear reduction in the frequency of occurrence of ozone loss saturation over the period 2001–2017 consistently throughout various datasets (e.g., ozonesonde and satellite measurements of ozone profiles and total columns), thereby revealing the emergence of an important milestone in ozone recovery. An emerging recovery in the Antarctic ozone hole The frequency of near-complete loss of ozone has become lower since 2001, suggesting that the recovery of the Antarctic ozone hole is underway. A team led by Jayanarayanan Kuttippurath at the Centre for Oceans, Rivers, Atmosphere and Land Sciences, Indian Institute of Technology Kharagpur, India, examined observations of ozone from meteorological balloons and satellites and found that, at 13–21 km above Antarctica, ozone began to reach near-zero levels as early as 1987 and continuing until the early 2000s. Since then, the frequency of near-zero ozone levels has begun to lessen. The ozone record is short and noisy, but the researchers clearly show that the peak of the ozone hole has ceased to worsen and is improving. Although full recovery of the ozone hole will take far longer, the findings are consistent with an expectation of ozone recovery following the reduction in ozone depleting substances mandated by the Montreal Protocol.